Impact of timing from last dose of dexamethasone administration to delivery, different steroid courses, and fetal number on preterm neonatal outcomes - Saifon Chawanpaiboon; Julaporn Pooliam; Monsak Chuchotiros (PLoS ONE, 2026)
Objectives To evaluate the impact of the timing from the last dose of dexamethasone to delivery, different steroid courses, and the number of fetuses (singleton vs twin) on preterm neonatal outcomes. This study focused on respiratory complications and associated conditions. Methods A retrospective analysis was conducted on 1800 pregnancies, comprising 1585 singleton pregnancies and 215 twin pregnancies, resulting in a total of 2015 neonates. The timing of dexamethasone administration relative to delivery was categorized into intervals: less than 6 hours, between 2 and 7 days, between 8 and 13 days, and 14 days or more. Neonatal outcomes, including respiratory distress syndrome (RDS), continuous positive airway pressure (CPAP) support, bronchopulmonary dysplasia (BPD), pneumothorax, and necrotizing enterocolitis (NEC), were analyzed. Multivariate logistic regression assessed the adjusted odds ratios (AORs) for these outcomes based on timing, steroid course (complete vs partial), and number of fetuses. Results Neonates exposed to dexamethasone between 2 and 7 days before delivery showed a reduced need for CPAP support (AOR: 0.65; 95% CI: 0.48–0.88). This group was compared to those exposed for less than 6 hours or more than 14 days before delivery. However, the incidence of RDS did not significantly decrease with the timing of dexamethasone administration. A higher incidence of pneumothorax was observed in neonates born less than 6 hours after an incomplete course (AOR: 1.89; 95% CI: 1.01–3.54). Twin pregnancies delivered within 12 hours of a complete course were at increased risk for NEC (AOR: 2.11; 95% CI: 1.07–4.16). Deliveries occurring more than 14 days after the last dose were associated with increased risks of ventilator support (AOR: 2.11; 95% CI: 1.08–4.11) and BPD. This was particularly evident in cases where multiple courses were administered. Conclusions The timing of the last dexamethasone dose is crucial for reducing respiratory complications other than RDS. The optimal window is between 2 and 7 days before delivery. This effect is influenced by the completeness of the steroid course and the number of fetuses. Tailoring dexamethasone administration according to these factors can significantly improve outcomes in preterm neonates, particularly in reducing the severity of respiratory complications. Thai Clinical Trials Registry (TCTR) number TCTR20230724002 (Registration date: 24 July 2023) http://thaiclinicaltrials.org/export/pdf/TCTR20230724002